Content analysis on the extent of partisanship among Cebu City-based local dailies in their news coverage of typhoon Yolanda, November 5, 2013- February 8, 2014 - Cabada, Aldwin C.; de Veyra, Grace Anne B. (Aldwin C. Cabada, Grace Anne B. de Veyra, Ma. Pia Vienna O. Pascasio, 2014)
On November 8, 2013, the entire Eastern Visayas Region was devastated by Super Typhoon Yolanda, the strongest typhoon that hit the Philippines in the 21st century. One of the primary issues that manifested before and after Typhoon Yolanda was the efficiency of the disaster preparedness strategies along with the relief and rehabilitation efforts undertaken by the Local Government Unit of Tacloban and the National Government. This in turn created conflict between two spheres of government and was one of the main issues reported by most media agencies all around the country, including the three local Cebu dailies: Cebu Daily News, The Freeman, and Sun Star Cebu.